Dermatomyositis Sine Myositis with Membranoproliferative Glomerulonephritis - Mohammad Bagher Owlia; Roya Hemayati; Shokouh Taghipour Zahir; Mohammad Moeini Nodeh (Case Reports in Rheumatology)
Dermatomyositis (DM) is an autoimmune disease that is characterized by involvement of proximal musculature and skin. We report a 52-year-old woman with a 6-year history of dermatomyositis sine myositis, who developed lower extremity edema and proteinuria. Pathological examination of renal biopsy showed membranoproliferative glomerulonephritis. She received steroid, cyclophosphamide, and mycophenolate mofetil. Over the 9 to 10 months after the beginning of treatment, the proteinuria was improved.